2016
DOI: 10.1016/j.atmosenv.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

SOA formation from naphthalene, 1-methylnaphthalene, and 2-methylnaphthalene photooxidation

Abstract: h i g h l i g h t sHigh SOA yields from 2-ring PAH photooxidation were found. Fractal-like and solid SOA was observed for the methylnaphthalene isomers during high NO x photooxidation. A m/z 104 peak was observed as a marker of phthalic acid from PAH photoxidation by HR-ToF-AMS analysis. a r t i c l e i n f o b s t r a c tThe SOA yield and chemical characteristics of SOA formation from naphthalene and two methyl substituted naphthalenes, 1-methylnaphthalene and 2-methylnaphthalene, were studied for high NO x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 50 publications
7
46
0
Order By: Relevance
“…Indeed, Shakya and Griffin (2010) proposed yields in the range of 0.08e0.16, while Chan et al (2009) determined yields to be 0.19e0.74. As discussed by Chen et al (2016), differences of SOA yields could be attributed to different chamber conditions such as light intensity, NO x levels, OH radicals, and organic mass loading. In the case of aromatic chemistry, it has been shown that photolysis processes play a major role in the loss of carbonyl products (Wang et al, 2006;Clifford et al, 2011).…”
Section: Soa Formationmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, Shakya and Griffin (2010) proposed yields in the range of 0.08e0.16, while Chan et al (2009) determined yields to be 0.19e0.74. As discussed by Chen et al (2016), differences of SOA yields could be attributed to different chamber conditions such as light intensity, NO x levels, OH radicals, and organic mass loading. In the case of aromatic chemistry, it has been shown that photolysis processes play a major role in the loss of carbonyl products (Wang et al, 2006;Clifford et al, 2011).…”
Section: Soa Formationmentioning
confidence: 96%
“…Although PAHs are potentially carcinogenic and mutagenic (Atkinson and Arey, 1994) some of their oxidation products present a larger toxicity than their parent hydrocarbons (Lin et al, 2005). Gas-phase products can partition to the particle phase and participate in SOA formation Kautzman et al, 2010;Shakya and Griffin, 2010;Kleindienst et al, 2012;Riva et al, 2015aRiva et al, , 2016Chen et al, 2016). A few studies have previously reported the importance of naphthalene gas phase photooxidation in SOA formation Kleindienst et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…The yield is higher than that for SOA formed from another bicyclic aromatic compound, naphthalene, which has a reported yield range of 0.04-0.73 under low-NO x conditions (Chan et al, 2009;Chen et al, 2016). The high yield suggests that the major fraction of indole oxidation products ends up in the particle phase at the concentrations used in this work.…”
Section: Properties Of Indole Soamentioning
confidence: 62%
“…The amount of the collected SOA material on each filter was estimated from SMPS data assuming 100 % collection efficiency by the filters and SOA material density of 1.4 g cm −3 . The density of indole SOA is unknown, but the adopted value of 1.4 g cm −3 is similar to the reported range of densities of 1.47-1.55 g cm −3 for SOA prepared from another bicyclic aromatic compound, naphthalene (Chan et al, 2009;Chen et al, 2016). In addition, densities of known indole oxidation products, for example isatin (1.47 g cm −3 ), anthranilic acid (1.40 g cm −3 ), indigo dye (1.20 g cm −3 ), isatoic anhydride (1.52 g cm −3 ), and 3-oxindole (1.20 g cm −3 ), range from 1.2 to 1.5 g cm −3 , suggesting that 1.4 g cm −3 should be a reasonable guess for indole SOA.…”
Section: Experimental Methodsmentioning
confidence: 68%
See 1 more Smart Citation